2018
DOI: 10.1080/09513590.2017.1416466
|View full text |Cite
|
Sign up to set email alerts
|

Women with inflammatory bowel diseases have a suboptimal cervical cancer screening rate and are not aware of the recommended human papilloma virus vaccine

Abstract: The aim of the study was to assess the self-reported cervical cancer screening rate among patients with inflammatory bowel diseases (IBD) and patient attitude towards human papilloma virus (HPV) vaccination. A self-designed survey was conducted in hospitalized IBD patients. The survey comprised demographic data, questions regarding cervical smear test frequency and vaccinations recommended for an IBD patient. Randomly, patients completed the survey with a physician present to determine question comprehension. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 18 publications
0
7
0
Order By: Relevance
“…Currently it is unclear whether the same effect can be expected in IBD patients, with or without immunosuppressive therapy. Regardless of a general awareness among gastroenterologists of an elevated risk of HPV-related neoplasia in IBD, screening for cervical cancer and HPV-vaccination in female IBD patients is still suboptimal [34].…”
Section: Discussionmentioning
confidence: 99%
“…Currently it is unclear whether the same effect can be expected in IBD patients, with or without immunosuppressive therapy. Regardless of a general awareness among gastroenterologists of an elevated risk of HPV-related neoplasia in IBD, screening for cervical cancer and HPV-vaccination in female IBD patients is still suboptimal [34].…”
Section: Discussionmentioning
confidence: 99%
“…A study by Long et al [54] revealed that only 70.4% of female IBD patients received cervical testing at least once every 3 years. In a recent study by Waszczuk et al [55], among 150 female IBD patients, only 69% reported of regular cervical testing (30% annually, 32% every 2-3 years, 7% every 5 years). Moreover, only 10% of female IBD patients were aware of the existing HPV vaccination recommendation.…”
Section: Human Papillomavirusmentioning
confidence: 96%
“…Women who are immunocompromised, as in IBD, have an increased risk of cervical dysplasia and cancer. 4 In a study involving 40 patients with IBD the incidence of abnormal smear was 42.5% versus 7% of controls. Women with IBD, women undergoing immunosuppressive treatment, or history of their use, have also a higher incidence of high-grade lesions in pap smear.…”
Section: Cervical Cancer Screeningmentioning
confidence: 97%
“…This study shows the importance of physicians cooperation in patient surveillance. 4 American College of Obstetrics and Gynaecology (ACOG) also recommends annual screening in resemblance to woman HIV positive. 6 However, a medical history of human papillomavirus (HPV) infection is not a formal indication for the suspension of immunosuppressive treatment.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation